Softening Shape Memory Polymer Substrates for Bioelectronic Devices With Improved Hydrolytic Stability - Hosseini, Seyed Mahmoud; Rihani, Rashed; Batchelor, Benjamin; Stiller, Allison M.; Pancrazio, Joseph J.; Voit, Walter E.; Ecker, Melanie (Frontiers in Materials, 2018)
Candidate materials for next generation neural recording electrodes include shape memory polymers (SMPs). These materials have the capability to undergo softening after insertion in the body, and therefore reduce the mismatch in modulus that usually exists between the device and the tissue. Current SMP formulations, which have shown promise for neural implants, contain ester groups within the main chain of the polymer and are therefore prone to hydrolytic decomposition under physiological conditions over periods of 11-13 months in vivo, thus limiting the utility for chronic applications. Ester free polymers are stable in harsh condition (PBS at 75 °C or NaOH at 37 °C) and accelerated aging results suggest that ester free SMPs are projected to be stable under physiological condition for at least seven years. In addition, the ester free SMP is compatible with microfabrication processes needed for device fabrication. Furthermore, they demonstrate in vitro biocompatible as demonstrated by high levels of cell viability from ISO 10995 testing.